Bacterial community of the brines extracted during the underground dissolution of potassium-magnesium salts of the Yakshinskoe deposit (Komi Republic, Russia) - A.A. Pyankova; E.G. Plotnikova; S.N. Shanina (Учёные записки Казанского университета: Серия Естественные науки, 2022)
This article provides the first description of the bacterial diversity in the Permian rock of the Upper Pechora salt basin. Halophilic and halotolerant bacteria of the classes Gammaproteobacteria (from the genera Halomonas, Marinobacter, and Idiomarina) and Actinomycetia (from the genus Dietzia) were isolated from the brines extracted during the underground dissolution of carnallite rocks in the pilot well of the Yakshinskoe deposit (Komi Republic, Russia) of potassium-magnesium salts. The analysis of 16S rRNA gene sequences cloned from the total DNA of the floatable part of the insoluble brine residues revealed the following bacterial classes: Gammaproteobacteria (closely related to the genera Idiomarina, Marinimicrobium, Marinobacter, Methylophaga, and Pseudidiomarina), Betaproteobacteria (phenologically similar to the genera Achromobacter and Methylotenera), as well as Alphaproteobacteria and Flavobacteriia (related to the genera Sulfitobacter and Salegentibacter, respectively). Several identified phylotypes (clones 113YS, 8YS, 150YS, and 157YS) had a low level of similarity with the closest type strains of the genera Methylophaga (M. nitratireducenticrescens JAM1T, 96.86%), Salegentibacter (S. salarius ISL-6T, 98.58%), and Methylotenera (M. versatilis 301T, 98.05% and 98.19%). This indicates that the brine samples contained new, previously undescribed, bacterial taxa. The results obtained define and shape the future prospects for studying the phylogenetic and functional diversity of microorganisms in the salt strata of the Yakshinskoe deposit.